Scaling behavior of VO2peak in trained wheelchair athletes - Goosey-Tolfrey, V. L.; Batterham, A. M.; Tolfrey, K. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: To examine the scaling behavior of peak oxygen uptake (VO2peak) in wheelchair athletes, adjusting for known covariates. METHODS: Body mass, VO2peak, and an estimate of adiposity (sum of four skinfolds) were determined in a sample of 45 highly trained wheelchair basketball and racing athletes. The participants were classified as possessing either "high" or "low" trunk stability and balance using recognized sporting classifications. A wheelchair ergometer was used to obtain the VO2peak measurements. The relationship between VO2peak and body mass was obtained via a nonlinear allometric model with the sum of four skinfolds, trunk stability and balance, and chronological age entered as covariates. RESULTS: The point estimate exponent for body mass was 0.82 (95% CI, 0.54-1.10). After controlling for the influence of body mass, adiposity, and age, the wheelchair athletes with greater trunk stability and balance had on average an 11% greater VO2peak. The regression model explained 54% of the sample variance in VO2peak. CONCLUSIONS: The obtained mass exponent of 0.82 is congruent with that predicted from the multiple-causes allometric cascade model and consideration of the physiological characteristics of spinal cord injured athletes. To compare the body size-independent VO2peak values of athletes within the study sample, the mass exponent of 0.82 may be adopted (i.e., mL x kg(-0.82) x min(-1)). The uncertainty in the point estimate, reflected in the relatively wide 95% CI, highlights the need for further research with larger samples to increase the precision of estimation.